Impacto do Sistema de Controle sobre a Venda de Novos Produtos - Valter Afonso Vieira; Juliano Domingues Silva; Sean Cassiolato Berbert; Valter da Silva Faia (RAC: Revista de Administração Contemporânea, 2015)
This paper’s main goal is to understand the impact of control systems on the relationship between a salesperson’s effort and their performance. The control systems have two perspectives: outcome and behavior. The difference between them is how a salesperson is evaluated in regards to their job. If the sales manager is only concerned with sales results, the control system is based on outcome. However, if the sales manager is concerned with a salesperson’s capacities, abilities and knowledge, the control system is based on behavior. Based on the theories developed by Anderson and Oliver (1987) and Oliver and Anderson (1994), we proposed a theoretical framework to explain sales performance, positioning the control system as a moderating variable. We undertook two descriptive field investigations to test the proposed model’s hypotheses for pharmaceutical sales representatives and car dealer salespersons. We estimated four regression equations to test the hypotheses. The first conclusion is that the perception of product innovation by salespeople actually influences the launch of new products. The second conclusion showed that salesperson effort has a negative relationship with performance. Third, we demonstrated the moderating effect control systems have on the relationship between salesperson experience and sales efforts.